Synthetic Biology: A Utilitarian Perspective - Smith, Kevin (Bioethics, 2013)
I examine the positive and negative features of synthetic biology (‘SynBio’) from a utilitarian ethical perspective. The potential beneficial outcomes from SynBio in the context of medicine are substantial; however it is not presently possible to predict precise outcomes due to the nascent state of the field. Potential negative outcomes from SynBio also exist, including iatrogenesis and bioterrorism; however it is not yet possible to quantify these risks. I argue that the application of a ‘precautionary’ approach to SynBio is ethically fraught, as is the notion that SynBio-associated knowledge ought to be restricted. I conclude that utilitarians ought to support a broadly laissez-faire stance in respect of SynBio.